The Effect of Consuming Ambon Banana (Musa paradisiaca Var. Sapientum) on Sleep Latency of Elderly Hypertension - Selvi Ria Ristania; Martianawati Martianawati; Stefanus Supriyanto; Rudi Irawan (Humanistic Network for Science and Technology (HNST), 2017)
Elderly hypertension often reported that their latency elongated was less compared to healthy elderly. The increase of latency impact on health, it causes susceptibility to illness, stress, confusion, disorientation, mood disorders, less fresh, decrease ability to make decisions. The aim of this research was to explain the effect of consuming Ambon banana on sleep latency of elderly hypertension in Mulyorejo, Surabaya. Time series one group pre-test post test design was used in this research. Affordable population in this research was elderly hypertension in RW 2 and RW 3 Mulyorejo Surabaya. Total sample was 15 respondents and taken by total sampling technique. The independent variable was consuming Ambon banana, and dependent variable was sleep latency of elderly hypertension. Every day the latency and blood pressure on elderly was monitored. Data was collected using questionnaire, and then analyzed using Wilcoxon Signed Rank Test. The result showed that consuming Ambon banana affect sleep latency (p=0.009). Keywords: Ambon banana, Sleep latency, Elderly hypertension